La presse architecturale, miroir actif de la préoccupation environnementale - Christophe Camus; Béatrice Durand (Communication)
What are the effects of sustainability on the coverage of architecture in the specialized trade press ? This study was based on a decade-long (2000-2009) analysis of articles in French architecture trade publications. The authors document the appearance and development of ecology as a permanent fixture in these professional forums, along with the resistance and changes it provoked. They contend that the issue of long-term ecological balance has had a profound effect on how professional publications refer to architectural production. In other words, they explore how different ways of talking about an architectural feature actually contribute to its very existence.